Numerical investigation of thermo-hydraulic transport characteristics of two-dimensional, steady flow through partially porous wavy channel. (16th December 2021) - Kumar, Prince; Pandey, Krishna Murari
Abstract: A comprehensive numerical analysis has been implemented to delineate the transport characteristics for flow of Newtonian fluid inside a channel with a porous slab and internal wavy walls. The heat transfer rate and pressure drop are observed to be augmented with the increasing Reynold number, Darcy number, and wavy wall's amplitude. Overall, change in Nusselt number and pressure drop is also assessed in relation to enhancement ratio and performance factor for the present wavy channel in comparison to the equivalent straight channel. Moreover, the enhancement ratio (ER) is greater than 7.5 for Da = 10 −5 and Re = 200 which attains maximum value of 10.8 for Da = 10 −2 and Re = 1200.